Delta Agropro Trading / Muhammad Khalis Mifzal Mohd Kamal - Mohd Kamal, Muhammad Khalis Mifzal (2020)
This case study is for ENT300 Fundamentals of Entrepreneurship which aims to expose students to the real business and help gain deeper understanding of business entrepreneurship. For this case study, I have chosen DELTA AGROPRO TRADING. His owner name Muhammad Kafeel Mubin bin Mohd Kamal. I also do the research about the product he sells to his customer. Main objective of his products is to aim local people to be more diligent in cooking on their own way. Some of his Personal Entrepreneurial Competencies (PECs) are productive, sees and acts on opportunities, concern for high quality of work and self-confidence. He also always tries to the best as an entrepreneur in his family.